2016
DOI: 10.1016/j.tecto.2016.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Syn- and postkinematic cement textures in fractured carbonate rocks: Insights from advanced cathodoluminescence imaging

Abstract: In calcite and dolomite deposits in fractures, transmitted light and optical cathodoluminescence methods detect crack-seal texture in some fractures, but scanning electron microscope-based cathodoluminescence (SEM-CL) combined with secondary-electron images and element maps, reveals crack-seal and cement growth textures where previous SEM-CL imaging methods found massive or featureless deposits. In a range of fractured carbonate rocks, patterns and textures of calcite and dolomite cements precipitated during a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 77 publications
(125 reference statements)
1
23
0
Order By: Relevance
“…The present work is an initial treatment of a highly coupled thermo-hydro-mechanical-chemical problem of vein formation as a result of cementation, wherein faceted crystal growth mechanisms based on the boundary conditions of synkinematic cementation are simulated. The present phasefield model needs to be extended in order to account for the mechanical forces for crack opening and chemical driving forces for crystal growth that facilitates the differential growth rates on facetted and unfacetted surfaces as suggested by Ukar and Laubach (2016). Provided the availability of physical parameters (e.g., crystal orientations, supersaturation of solute, absolute rates of calcite accumulation) through benchmark cement growth experiments, the model can be calibrated to precisely mimic the experimentally synthesized veins and further explore the controls on fabric development in natural veins.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present work is an initial treatment of a highly coupled thermo-hydro-mechanical-chemical problem of vein formation as a result of cementation, wherein faceted crystal growth mechanisms based on the boundary conditions of synkinematic cementation are simulated. The present phasefield model needs to be extended in order to account for the mechanical forces for crack opening and chemical driving forces for crystal growth that facilitates the differential growth rates on facetted and unfacetted surfaces as suggested by Ukar and Laubach (2016). Provided the availability of physical parameters (e.g., crystal orientations, supersaturation of solute, absolute rates of calcite accumulation) through benchmark cement growth experiments, the model can be calibrated to precisely mimic the experimentally synthesized veins and further explore the controls on fabric development in natural veins.…”
Section: Discussionmentioning
confidence: 99%
“…This interplay determines the morphological attributes of the resulting veins based on the crack opening rates (Mügge 1928;Urai et al 1991) and was shown to affect quartz-bearing veins (e.g., Laubach 1988;Lander and Laubach 2015), calcite veins (Hilgers et al 2001), and carbonate veins in dolostones (Gale et al 2010). Carbonate vein textures can also be subject to an interplay of synand postkinematic cementation (Ukar and Laubach 2016). The analysis of microtextures using e.g., a cathodoluminescence detector mounted on a scanning electron microscope (SEM-CL) might highlight the different cement generations (e.g., Ukar and Laubach 2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is useful as an imaging tool for characterising zonation, alteration, and growth patterns, although we note that the contrast in zonation largely reflects variations in major element composition, and as such it is typically less sensitive than CL. Ukar and Laubach (2016) provide a recent review of high spatial-resolution scanning electron microscope (SEM)-based imaging of vein-filling calcite mineralisation.…”
Section: Non-destructive Techniquesmentioning
confidence: 99%
“…In contrast to metamorphic and hydrothermal veins, many partly cemented fractures in diagenetic settings contain considerable porosity (Figure ). Although in most respects these fractures that form under cooler conditions do not resemble “crack seal veins,” textures resembling those found in vein deposits occur as highly localized fracture cement deposits (e.g., Evans & Bartholomew, ; Evans & Battles, ; Evans et al, ; Laubach, ; Laubach, Olson, et al, ; Laubach, Reed, et al, ; Ukar & Laubach, ; Urai et al, ). The precipitating crystals in these fractures include a range of phases and have a rich variety of morphologies and can be fibrous, elongate, blocky, or veneers (rinds) that line fracture pore space (Ankit et al, ; Lander & Laubach, ).…”
Section: Why Chemistry Is Important In Understanding Formation and Evmentioning
confidence: 99%